A modest proposal for restoration ecology. Issue 3 (7th May 2019) - Brick, Cameron
Abstract : Restoration ecology struggles to mitigate human‐caused ecological damage. Non‐native species are a particular challenge. This article describes two restoration attempts following introduced species in California and then makes a radical culling proposal. Environmental regulations, legal protections, and restoration projects are necessary to preserve ecosystem services, but such policies are often unpopular. Restorers often struggle when public opinion opposes evidence‐based practice, and this occurs particularly when the interventions involve killing mammals. Therefore, restoration efforts may benefit from more attention to how individuals perceive the acceptability of environmental policies and how to communicate policy options effectively for individuals to make informed decisions. Restoration ecology can follow the recent shift of medicine away from imperatives and toward informed patient choice. Restoration projects may benefit from recent advances in psychology and communication that help individuals make policy decisions that align with their personal values.